Nanostructures and Nanomaterials for Batteries Principles and Applications - Guo, Yu-Guo (Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the roles of nanostructures and nanomaterials in the development of battery materials for state-of-the-art electrochemical energy storage systems, and provides detailed insights into the fundamentals of why batteries need nanostructures and nanomaterials. It explores the advantages offered by nanostructure electrode materials, the challenges of using nanostructured materials in batteries, as well as the rational design of nanostructures and nanomaterials to achieve optimal battery performance. Further, it closely examines the latest advances in the application of nanostructures and nanomaterials for future rechargeable batteries, including high-energy and high-power lithium ion batteries, lithium metal batteries (Li-O2, Li-S, Li-Se, etc.), all-solid-state batteries, and other metal batteries (Na, Mg, Al, etc.). It is a valuable reference resource for readers interested in or involved in research on energy storage, energy materials, electrochemistry and nanotechnology.